2018
DOI: 10.20944/preprints201810.0570.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Butyrate Stimulates Histone H3 Acetylation, RANKL Expression, But Inhibited Osteoprotegerin Expression/Secretion in MG-63 Osteoblastic Cells

Abstract: Butyric acid as a histone deacetylase (HDAC) inhibitor was produced by a number of periodontal and root canal microorganisms (such as Porphyromonas, Fusobacterium etc.). Butyric acid may affect the biological activities of periodontal/periapical cells such as osteoblasts, periodontal ligament cells etc., and thus affect periodontal/periapical tissue destruction and healing. The purposes of this study were to study the toxic effects of butyrate on matrix and mineralization markers’ expression of MG-63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The results showed that the proportion of bacteria involved in butyric acid production significantly decreased in the osteoporosis and osteopenia groups than the control group. Butyric acid can regulate bone metabolism in various ways (45,46). It was reported that people with metabolic diseases and inflammatory diseases usually have low levels of butyrate-producing bacteria in their intestines (47), and that inflammatory cytokines can enhance osteoclast activity, leading to a decrease in bone mass (48).…”
Section: Disscussionmentioning
confidence: 99%
“…The results showed that the proportion of bacteria involved in butyric acid production significantly decreased in the osteoporosis and osteopenia groups than the control group. Butyric acid can regulate bone metabolism in various ways (45,46). It was reported that people with metabolic diseases and inflammatory diseases usually have low levels of butyrate-producing bacteria in their intestines (47), and that inflammatory cytokines can enhance osteoclast activity, leading to a decrease in bone mass (48).…”
Section: Disscussionmentioning
confidence: 99%
“…9 Chung MC et al found in their study that butyric acid affects periodontal destruction and healing. 10 In periodontal disease, there is marked decrease in the level of formic acid, lactic acid, alpha amino butyric acid and formic acid. There is drastic decrease in the level of lactic acid that indicates change in the level of commensal bacteria i.e.…”
Section: Metabolical Changes In the Oral Fluidmentioning
confidence: 99%